2022
DOI: 10.1093/jacamr/dlab197
|View full text |Cite
|
Sign up to set email alerts
|

Activity of cefepime/taniborbactam and comparators against whole genome sequenced ertapenem-non-susceptible Enterobacterales clinical isolates: CANWARD 2007–19

Abstract: Objectives This study assessed in vitro activities of cefepime/taniborbactam and comparator antimicrobial agents against ertapenem-non-susceptible Enterobacterales (ENSE) clinical isolates collected from the CANWARD study 2007–19, and associations between MIC and various mechanisms of β-lactam resistance identified using WGS. Methods A total of 179 ENSE (MIC ≥ 1 mg/L) isolates underwent susceptibility testing using reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The potent activity of cefepime-taniborbactam against KPC-, OXA-48-like-, ESBL-, and AmpC-positive Enterobacterales was observed in earlier, limited studies focusing on challenge sets of isolates ( 9 11 , 15 , 16 ). A study of 247 carbapenemase-producing Enterobacterales from Spain reported cefepime-taniborbactam MICs of ≤16 μg/mL for 98.5% (199/202) of serine carbapenemase-positive and 93.3% (42/45) of MBL-positive isolates ( 12 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The potent activity of cefepime-taniborbactam against KPC-, OXA-48-like-, ESBL-, and AmpC-positive Enterobacterales was observed in earlier, limited studies focusing on challenge sets of isolates ( 9 11 , 15 , 16 ). A study of 247 carbapenemase-producing Enterobacterales from Spain reported cefepime-taniborbactam MICs of ≤16 μg/mL for 98.5% (199/202) of serine carbapenemase-positive and 93.3% (42/45) of MBL-positive isolates ( 12 ).…”
Section: Discussionmentioning
confidence: 76%
“…In that study, bla NDM-5 -positive E. coli (76.1%, 35/46) were the majority of the isolates with elevated cefepime-taniborbactam MICs, and almost all isolates of this subset had a YRIN or INYR insertion in PBP3, suggesting that PBP3 insertions were associated with elevated cefepime-taniborbactam MICs, as taniborbactam is known to inhibit NDM-5 (9). Canadian investigators identified two isolates of E. coli with cefepime-taniborbactam MICs of >16 μg/mL (32 μg/mL) among a set of 179 ertapenem-nonsusceptible isolates from over a decade of nationwide resistance surveillance; 1 possessed NDM-5, OXA-181 and TEM-1B, an OmpC alteration and a YRIN insertion in PBP3, while the second contained CTX-M-71, a truncated OmpF and a large alteration in OmpC ( 11 ). A study of Enterobacterales with cefepime-taniborbactam MICs of >8 μg/mL noted no universal resistance mechanism across the isolates tested but, rather, combinations of carbapenemases (e.g., NDM-5, NDM-7) with PBP3 insertions and/or porin changes ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though taniborbactam has been reported to possess potent inhibitory activity (50% inhibitory concentration [IC 50 ]) against the purified NDM variants and many ESBLs ( 28 ), higher MICs obtained against E. coli producing NDM and OXA-48-like or NDM alone led us to undertake an additional investigation. Based on previous publications ( 29 31 ), we analyzed PBP3 for the presence of 4-amino-acid insertions among E. coli isolates and found that an overwhelming proportion of isolates (97%) harbored the inserts regardless of the carbapenemase type. It has been reported previously that those β-lactams that heavily rely on the PBP3 engagement for their antibacterial action are adversely impacted by the presence of amino acid inserts in PBP3 of E. coli ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication by Golden et al ., 1 resistance to cefepime/taniborbactam was observed in an NDM-expressing Escherichia coli harbouring a four-amino acid insertion in PBP3. This particular combination of resistance mechanisms seems to be an emerging threat.…”
mentioning
confidence: 99%
“…Very disturbingly, published studies as well as our laboratory studies (unpublished) hint that even cefiderocol and cefepime/taniborbactam would have limited activity against E. coli with these dual resistance mechanisms. 1 , 6 Plazomicin has been shown to exhibit inconsistent activity against NDM producers. 7 Cefepime/zidebactam is highly active against these organisms but is in clinical development.…”
mentioning
confidence: 99%